IMPLEMENTASI COMPUTER VISION UNTUK MENANGKAP CITRA KENDARAAN DALAM PENERAPAN PARKIR CASHLESS DI BATAM - M Ikhlasul Akbar; Amrizal (Computer Science and Industrial Engineering, 2024)
This study aims to create an automatic parking system using Computer Vision technology to reduce vehicle flow congestion in parking areas, specifically in Batam. Traffic congestion in parking areas is a common issue in Batam, and the application of Deep Learning technology, especially Computer Vision, is expected to address this problem. Vehicle image data is collected, cleaned, and labeled to facilitate the training process of the YOLO v8 model. The model is then tested with existing data and further tested using a camera. Through this system update, it is hoped to assist parking management in minimizing vehicle flow congestion in parking areas.